Milk coagulation ability of Rendena and Holstein-Friesian cattle breeds - Varotto, Alice; Marchi, Massimo De; Penasa, Mauro; Cassandro, Martino (Acta Agraria Kaposváriensis, 2014)
Aim of this study was to compare Holstein-Friesian (HF) and Rendena (RE) cattle breeds for milk coagulation and composition traits predicted by mid-infrared spectroscopy using official milk recording samples of 28 single-breed dairy herds of northeast Italy. Individual milk samples (n = 3,622) from 1,786 cows were analyzed for rennet coagulation time (RCT, min), curd firmness (a30, mm), and composition traits. A linear mixed model was used to study the effect of breed and environmental factors on RCT and a30. Breed was the most important source of variation for coagulation traits. In particular, milk from RE coagulated earlier and showed a firmer curd than milk from HF cows. Rennet coagulation time was shortest at the beginning of lactation, and a30 was better at the beginning and end of lactation. In conclusion, RE produced milk more suitable for cheese processing than that of HF. Clotting characteristics of RE breed should be considered when developing strategies useful for the valorization of this local genetic resource.
Keywords: milk coagulation ability; dairy cattle breed; mid-infrared spectroscopy